2009
DOI: 10.1007/s00586-009-0939-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic evaluation on quality management in spine surgery

Abstract: Health care expenditures are substantially increasing within the last two decades prompting the imperative need for economic evaluations in health care. Historically, economic evaluations in health care have been carried out by four approaches: (1) the human-capital approach (HCA), (2) cost-effectiveness analysis (CEA), (3) cost-utility analysis (CUA) and (4) cost-benefit analysis (CBA). While the HCA cannot be recommended because of methodological shortcomings, CEA and CUA have been used frequently in healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…This is not surprising, given the recent explosion in number of spine procedures being performed and the emerging markets for spinal implants. 4,35 Hydrocephalus, which continues to be a major problem (particularly in the field of pediatric neurosurgery), has also seen growth but maintains overall small numbers of publications. While functional and vascular neurosurgery have only experienced modest growth overall, expansion of publications in the subfields of deep brain stimulation and endovascular techniques demonstrate innovation and high productivity, respectively, with regard to novel approaches and techniques.…”
Section: Growthmentioning
confidence: 99%
“…This is not surprising, given the recent explosion in number of spine procedures being performed and the emerging markets for spinal implants. 4,35 Hydrocephalus, which continues to be a major problem (particularly in the field of pediatric neurosurgery), has also seen growth but maintains overall small numbers of publications. While functional and vascular neurosurgery have only experienced modest growth overall, expansion of publications in the subfields of deep brain stimulation and endovascular techniques demonstrate innovation and high productivity, respectively, with regard to novel approaches and techniques.…”
Section: Growthmentioning
confidence: 99%
“…Accurate placement of instrumentation is critical to avoid iatrogenic morbidity. [ 20 23 25 ] Surgical intervention for spinal pathologies has grown tremendously over the recent years.,[ 4 18 30 ] and has been accompanied by an increase in the incidence of revision spine surgery and arthrodesis. [ 18 ] The current study's aim is to look at the currently published data on the costs and efficacy of spinal navigation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Soegaard et al 8 investigated patient characteristics that infl uenced the cost-effectiveness of lumbar fusion at 2 years. Smoking and a diagnosis of previous spinal surgery were both signifi cantly associated with poorer clinical outcome, increased costs, and a reduction in net benefi t. Another recent economic analysis found that advanced age, diabetes, and obesity were associated with higher hospital costs for patients who underwent spinal surgery.…”
mentioning
confidence: 99%